Role of Interdiffusion and Segregation during the Life of Indium Gallium Arsenide Quantum Dots, from Cradle to Grave - Thomas Walther (Nanomaterials, 2022)
This article summarizes our understanding of the interplay between diffusion and segregation during epitaxial growth of InGaAs and InAs quantum dots. These quantum dots form spontaneously on flat GaAs (001) single-crystalline substrates by the so-called Stranski-Krastanow growth mechanism once a sufficient amount of indium has accumulated on the surface. Initially a perfectly flat wetting layer is formed. This strained layer then starts to roughen as strain increases, leading first to small, long-range surface undulations and then to tiny coherent islands. These continue to grow, accumulating indium both from the underlying wetting layer by lateral indium segregation and from within these islands by vertical segregation, which for InGaAs deposition results in an indium-enriched InGaAs alloy in the centre of the quantum dots. For pure InAs deposition, interdiffusion also results in an InGaAs alloy. Further deposition can lead to the formation of misfit dislocations that nucleate at the edges of the islands and are generally sought to be avoided. Overgrowth by GaAs or InGaAs alloys with low indium content commences preferentially between the islands, avoiding their strained edges, which initially leads to trench formation. Further deposition is necessary to cap these quantum dots effectively and to re-gain an almost flat surface that can then be used for subsequent deposition of multiple layers of quantum dots as needed for many optoelectronic devices.